Pattern and Management Outcome of Chest Injuries in Omdurman Teaching Hospital (Global Journal of Medical Research, 2015)
Background : Thoracic trauma is one of the leading causes of morbidity and mortality in developing countries. The incidence of thoracic trauma has rapidly increased in this century of high speed vehicles, violence and various other disasters. A considerable number of preventable deaths occur due to inadequate or delayed treatment of otherwise an easily remediable injury. Objectives : to study Pattern and management outcome of chest injuries in Omdurman Teaching Hospital. Patients and methods: This study is Observational prospective analytical hospital based study,conducted in Omdurman Teaching Hospital of one year duration from May 2013 to April 2014 in which patients with significant thoracic trauma were managed ,questionnaires were used and variables were Age, gender, mechanism of injury, clinical diagnosis, associ ated injuries, complications, treatment, length of hospital stay.
Keywords: chest injuries; pneumothorax; thoracostomy; management; pattern; chest tube